Perbaikan Sistem Pemenuhan Order pada Pabrik Garment PT X - Andrew Benjamin Kosasih (Jurnal Titra, 2020)
PT X is a garment company based in Surabaya. Currently, it has a conventional and unstructured order fulfillment system. This condition caused uncertainty in product delivery and causing customer complaints. The company is managed by a director, vice director, and administration staff. It also only has a production and quality control department. Customer orders are produced in a make-to-order system which means that production in PT X have a high variety. A new order fulfillment system is proposed to help the company to have a more structured and organized system so customer complaints can be minimized and raise the customer’s satisfaction. The suggested system started with the order receiving process until the product is sent to the customer. New standardized documents are also created for the new system and a few improvement on production process is added. Steps on how to implement the new system are also suggested to help the company on adapting the new system.